PENINGKATAN MUTU DAN KUANTITAS PRODUKSI GERABAH PADA INDUSTRI PEMBUATAN GERABAH DI MALANG JAWA TIMUR - Mochamad Arif Irfa’i, Nova Kristiana, Muchlis Arif, Tri Sudarwanto (Universitas Hasyim Asy'ari, 2019)
The aims of this activity is the application of furnace and pottery design training to help improve the quality and quantity pottery products. The methods of implementing this activity is the implementation team analyzes the problems of the partner team (Mr. Suhartoko). The results of the analysis revealed that Mr. Suhartoko’s pottery business still used wood-burning stoves, ability to design pottery motifs (grading techniques) that are underdeveloped and marketing management that has not been managed optimally. Based on the results of discussions and request of partner teams. Then the design is carried out for the manufacture of controlled system furnaces. Training preparation to design pottery motifs (grading techniques) and marketing workshops. At the end of the activity the community partnership program was facilitated and evaluated. The results of the community partnership program activities are an increase in the quality of pottery products after using a controlled furnace system. While still using the manual furnace, the pottery produced is only made of clay after using a controlled furnace system. The pottery produced is capable of producing pottery made of ceramics. In quantity, there was an increase in the production of pottery, which were from 8-10 pottery each time it processed to 22-24 pottery. While, in terms of design, pottery motifs have started to develop and are able to selling high. The indicator is that the selling price of pottery products increases from 10 thousand rupiahs to 15 thousand rupiahs for each pottery product to 100 thousand rupiahs to 150 thousand rupiahs for each pottery product. At this time, Pottery product marketing has also begun to penetrate the gallery, hotel and café.